Creating ‘automatic subjects’: Corporate wellness and self-tracking - Till, Christopher (Health (London, England : 1997), 2019)
The use of self-tracking devices has increased dramatically in recent years with enthusiasm from the public as well as public health officers, healthcare providers and workplaces seeking to instigate behaviour change in populations. Analysis of the ontological principles informing the design and implementation of the Apple Watch and corporate wellness programmes using self-tracking technologies shows that their primary focus is on the capture and control of attention rather than material health outcomes. Health, wellness and happiness have been conflated with productivity, which is now deemed to be dependent on the harnessing of libidinal as well as physical energy. In this context, self-tracking technologies and related corporate wellness interventions have been informed by ‘emotional design’, neuroscientific and behavioural principles which target the ‘pre subjective’ consciousness of individuals through manipulating their habits and neurological functioning. This article draws on the work of Bernard Stiegler to suggest framing self-tracking as ‘industrial temporal objects’, which capture and ‘short circuit’ attention. It is proposed that a central aim is to ‘accumulate the consciousnesses’ of subjects consistent with the methods of a contemporary ‘attention economy’. This new logic of accumulation informs the behaviour change strategies of designers of self-tracking devices, and corporate wellness initiatives, taking the form of ‘psychotechnologies’ which attempt to reconstruct active subjects as automatic and reactive ‘nodes’ as part of managed networks.